Vortex shedding and evolution induced by the interactions between a solitary wave and a submerged horizontal plate. Issue 2 (4th March 2022) - Ai, Congfang; Ma, Yuxiang; Yuan, Changfu; Xie, Zhihua; Dong, Guohai; Stoesser, Thorsten
Abstract : This paper presents results of a solitary wave propagating over a submerged horizontal plate based on a non-hydrostatic model. A high-resolution advection scheme is employed based on a second-order flux-limiter method. The model is first validated by comparing numerical results with recently obtained measured data. Then, a series of simulations are carried out to investigate the effect of the plate length on the characteristics of vortex shedding and evolution. With the increase in the length of the plate, more dominant vortical structures induced by the solitary wave with the same wave height can be identified near the lee side of the plate. There are two separate positive vortex shedding from the lower corner of the plate near the lee side, which are not presented in experiments. The secondary positive vortex leads to the water surface deformation for the case that is close to the limit when wave breaking occurs.